Loob at kapwa in action: analysis of "Wanted sa Radyo" in sociocultural context - Ramos, Chenny V.
With more than 20 million subscribers on YouTube, Raffy Tulfo has arguably become the most influential personality in the country today. In his public service show "Wanted sa Radyo", he helps people, especially the poor and marginalized groups, to express their concerns against certain individuals in the hopes to get justice. Earlier critical essays suggested that the Tulfo phenomenon rose due to the state's failure to give the basic needs of its people. Thus, the public had to look for an alternative institution, such as the media, that can provide them with such necessities. However, this conclusion neglected the sociocultural factors that contributed to the rise of such institutions. To fill the gap, the researcher used Sikolohiyang Pilipino to explain the popularity of "Wanted sa Radyo" in the Philippine society. Using the qualitative methods of discourse analysis, the author discovered that the popularity of "Wanted sa Radyo" is anchored on Filipino values of loob (kagandahang loob, utang na loob, and lakas ng loob) and kapwa (karangalan, kalayaan, and katarungan). Thus, media products, such as public service programs are not just creators and senders of national narratives, but they can also help in the social order.